(untitled) (Collection of scientific works «Modern structures of metal and wood», 2019)
Choice of arrangement for steel bar system reinforcing is considered a multivariate task. The current development level of methods for calculating and designing structures, the variety of possible arrangements and reinforcement methods allow to develop a general approach to problems concerning reinforcement optimizing of steel structures. All this envisages calculation and design of structural reinforcement according to a certain arrangement with predetermined parameters and under known influences. Only experimental results are able to confirm validity of the adopted arrangement for strengthening or flattening of structures. The methods for research of steel double-T members bearing resistance after primary loading, unloading, subsequent flattening and secondary loading are described. Samples of various types of residual stress state control were used as experimental ones. After primary compression testing, the experimental samples were flattened by press or by means of idler spindle beading along bulging edges. The results of experimental determination of samples bearing resistance after unloading and flattening are presented. The test results displayed that the bearing resistance of the most samples after flattening was no lower than the samples bearing capacity obtained during initial tests. The research results were used to justify possible further operation of the warehouse building columns. The need for work is caused by the fact that during operation, when moving goods on the floor, damage occurred to individual columns in form of bent flanges or dents in the flanges. For three columns, the curvature exceeded the maximum permissible values. It was found according to the calculation results, that the most loaded column, with a dent in the flange in its lower part, had a significant margin of safety. Guidance for ensuring the long and safe operating life of columns is developed. For this purpose, it was proposed to flatten the flanges by means of hydraulic jacks. Reinforcement of structures was executed on location.